Number needed to treat in indirect treatment comparison. (14th March 2018) - Guyot, Patricia; Cheng, Wei; Tremblay, Gabriel; Copher, Ronda; Burnett, Heather; Li, Xuan; Makin, Charles
Aim: For dichotomous outcomes, odds ratio (OR) is one of the usual summary measures of indirect treatment comparison. A corresponding number needed to treat (NNT) estimate may facilitate understanding of the treatment effect.Methods: We show how to estimate NNT based on OR results of a matching adjusted indirect comparison. We also have derived the explicit formula of its 95% CIs by applying the delta method, and as an alternative, a simulation-based method.Results: The method was applied in a case study example in radioiodine-refractory differentiated thyroid cancer (RR-DTC) patients, comparing lenvatinib to sorafenib. For every two RR-DTC patients treated with lenvatinib instead of sorafenib, one fewer would have progressed and for every eight RR-DTC patients treated with lenvatinib instead of sorafenib, one fewer would have died.Conclusion: Using NNT to summarize the results of a matching adjusted indirect comparison can help the clinicians to better understand the results in addition to OR.